Aquaporin-1 Translocation and Degradation Mediates the Water Transportation Mechanism of Acetazolamide - Zhang, Jianzhao; An, Yu; Gao, Junwei; Han, Jing; Pan, Xueyang; Pan, Yan; Tie, Lu; Li, Xuejun (PLOS ONE, 2012)
Background Diuretic agents are widely used on the treatment of water retention related diseases, among which acetazolamide (AZA) acts originally as a carbonic anhydrase (CA) inhibitor. Aquaporin-1 (AQP1) being located in renal proximal tubules is required for urine concentration. Previously our lab has reported AZA putatively modulated AQP1. Aim of this study is to testify our hypothesis that regulating AQP1 may mediate diuretic effect of AZA. Methodology/Principal Findings For in vivo study, we utilized Sprague Dawley rats, as well as AQP1 knock-out (AQP1−/−) mice to examine urine volume, and human kidney-2 (HK-2) cell line was used for in vitro mechanism study. In our present study we found that AZA decreased CAs activity initially but the activity gradually recovered. Contrarily, diuretic effect was consistently significant. AQP1 protein expression was significantly decreased on day 7 and 14. By utilizing AQP1−/− mice, we found diuretic effect of AZA was cancelled on day 14, while urine volume continuously increased in wild-type mice. Surface plasmon resonance (SPR) results indicated AQP1 was physiologically bound by myosin heavy chain (MHC), immunoprecipitation and immunofluorescence results confirmed this protein interaction. In vitro study results proved AZA facilitated AQP1 translocation onto cell membrane by promoting interaction with MHC, dependent on ERK/ myosin light chain kinase (MLCK) pathway activation. MHC inhibitor BDM and ERK inhibitor U0126 both abolished above effect of AZA. Eventually AZA induced AQP1 ubiquitination, while proteasome inhibitor MG132 reversed AZA's down-regulating effect upon AQP1. Conclusions/Significance Our results identified AZA exerted diuretic effect through an innovative mechanism by regulating AQP1 and verified its inhibitory mechanism was via promoting MHC-dependent translocation onto cell membrane and then ubiquitin mediated degradation, implicating a novel mechanism and target for diuretic agent discovering.